LANDSLIDE VULNERABILITY ANALYSIS BASED ON THE SEISMIC VULNERABILITY INDEX USING THE HVSR MICROTREMOR METHOD ON CLIFF AREAS IN HANURA VILLAGE, TELUK PANDAN DISTRICT, PESAWARAN REGENCY - Permanasari, Ikah Ning Prasetiowati; Ba’asyir, Indi Nurazizah; Setiawan, Muhamad Ragil; Pardede, Indra; Monica, Yeli (Indonesian Physical Review, 2025)
Way Ratai Road in Pesawaran Regency connects tourist areas managed by the Lampung Provincial Government. This road has cliffs with steep slopes, which have the potential to cause landslides. This research is very important because Way Ratai road is the only access road to Pesawaran beach tourism which is the main tourist destination of Lampung Province. Moreover, Way Ratai road is also the only access road connecting to the provincial capital of Bandar Lampung. This research was conducted to determine the soil vulnerability to seismic vibration on two cliffs around Way Ratai Road, Teluk Pandan District, Pesawaran Regency. The method used was microtremor signal recording with the Horizontal Vertical to Spectral Ratio (HVSR) method to determine the amplification factor (), dominant frequency (), sediment thickness (H), and seismic vulnerability index (Kg). The first cliff's measurement and data processing results showed an amplification factor () value of 2.74 - 3.70, a dominant frequency () of 3.75 - 4.56 Hz, a sediment thickness (H) of 14.09 m, and a seismic vulnerability index (Kg) of 2.39 m²/s. On the second cliff, the results showed an amplification factor () value of 2.27 - 3.40, a dominant frequency () of 3.54 - 7.20 Hz, a sediment thickness (H) of 9.33 m, and a seismic vulnerability index (Kg) of 1.84 m²/s. In term of seismic vibration, both cliffs, prone to landslides, have high stability against seismic vibrations. In the event of a landslide on these two cliffs, the estimated slip surface on the first cliff would be translational, and the second cliff would be a combination of translational and slight rotational, with an estimated volume of soil that could potentially slide on the first cliff is 30,492.16 m³ and on the second cliff, it is 27,188.92 m³.